Dapatkah game digital menurunkan beban kognitif? Tinjauan sistematis dan meta-analisis pada pembelajaran matematika - Seftia Kusumawardani; Agus Efendi; Sri Sumaryati (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2025)
Mathematics learning often burdens students' cognitive capacity, hindering their understanding of concepts and mastery of the material. Digital Game-Based Learning (DGBL) offers a promising approach to address this challenge, but its effectiveness remains a subject of debate. This research employs a Systematic Literature Review and meta-analysis to analyze 15 empirical studies. The primary objective is to evaluate the impact of DGBL on cognitive load, identify research trends, and determine the factors that moderate its effectiveness. The meta-analysis definitively demonstrates that DGBL has a significant and medium effect on reducing students' cognitive load in mathematics learning. Further analysis reveals that the type of mathematics content and game genre act as significant moderators. Specifically, DGBL exhibits superior effectiveness in reducing cognitive load with algebra and geometry material compared to arithmetic, percentages, patterns, number lines, and graphs. Moreover, simulation and puzzle genres prove more effective than role-playing and adventure genres. This research highlights the importance of carefully considering the selection of content and game genre when implementing DGBL to optimize the reduction of cognitive load in elementary schools. These findings provide valuable insights for educators and educational software developers in designing more effective learning interventions tailored to students’ needs.